INTELLIGENCE QUALITY IN VERONICA ROTH’S ALLEGIANT - Allen Dicson Tampi; Imelda Lolowang (KOMPETENSI, 2021)
This study aims to determine the intelligence quality revealed in Veronica Roth's Allegiant. The researchers conduct this study by using qualitative research based on Lincoln, and the data collection uses two ways: Primary sources and secondary sources. The primary data collection are from the novel, and secondary data collection use references from articles, journals, books, and the internet. In analyzing the data, the researchers use a reader-response approach based on Cagri Tugrul Mart. Intelligence quality talks of how well a person's intelligence excels. Intelligence can apply to many contexts, such as intelligence in strategy and intelligence in survival. Their qualities can be assessed by how well the performance and the achievements gained. The results of this study show that Tris, the main character, used her intelligence qualities against the leader of the city of Chicago, Evelyn, and the leader of the Genetic Welfare Bureau, David. When Evelyn became the new city leader, the people expected her could stop the disputes between factions. However, Evelyn used her power for other purposes. Tris felt she had to do something to stop Evelyn from her act of cruelty that ruled over the city by unilateral decisions. Tris also joined the Allegiant group to fight Evelyn and left the city to find out the truth about the factions. When Tris and her friends managed to get out of town, they met David. David told all the truth about the existing faction system. He also told Tris that the Bureau would use memory serums on the people in the city to erase their memories and reorganize their memories according to the Bureau's wishes. Tris and her friends tried to stop David from executing his plans. In the end, they successfully stopped David and saved the city of Chicago